CONTINUING EDUCATION AND PROFESSIONALIZATION IN POST-MEDIUM COURSES IN EDUCATIONAL ROBOTICS - Marinho Martins, Dayse; Abreu Cunha, Natália; Regina Corrêa Garcez, Claudia (Revista Gênero e Interdisciplinaridade, 2023)
Approach to Technical Post-Secondary Courses, aiming to analyze the perspectives of the offer as a policy to promote continuing education in the field of professional education, aimed at graduates of technical courses at secondary level. It presents the characterization of the courses and the implementation process, as well as training possibilities in the field of educational robotics. The qualitative research, based on the critical dialectical framework, was based on the theoretical contributions of Gramsci regarding the perspective of a unitary school and Candau regarding the notion of continuing education. Bibliographical research was carried out, complemented by documental research encompassing legislation on Professional and Technological Education, obtained through the Planalto Legis application. Post-medium courses seek to equip technical professionals to carry out specialized services and present notions, fundamentals and practices based on entrepreneurial conduct, permeated by innovation, ethics and social responsibility. In addition, they refine the training of graduates from technical courses, raising opportunities for professional improvement, and, consequently, the human development index, articulating science and innovation, especially in the field of educational robotics.